Typical atrial flutter: Diagnosis and therapy - Thomas, Dierk; Eckardt, Lars; Estner, Heidi L; Kuniss, Malte; Meyer, Christian; Neuberger, Hans-Ruprecht; Sommer, Philipp; Steven, Daniel; Voss, Frederik; Bonnemeier, Hendrik (Herzschrittmachertherapie & Elektrophysiologie, 2016)
Typical, cavotricuspid-dependent atrial flutter is the most common atrial macroreentry tachycardia. The incidence of atrial flutter (typical and atypical forms) is age-dependent with 5/100,000 in patients less than 50 years and approximately 600/100,000 in subjects > 80 years of age. Concomitant heart failure or pulmonary disease further increases the risk of typical atrial flutter.Patients with atrial flutter may present with symptoms of palpitations, reduced exercise capacity, chest pain, or dyspnea. The risk of thromboembolism is probably similar to atrial fibrillation; therefore, the same antithrombotic prophylaxis is required in atrial flutter patients. Acutely symptomatic cases may be subjected to cardioversion or pharmacologic rate control to relieve symptoms. Catheter ablation of the cavotricuspid isthmus represents the primary choice in long-term therapy, associated with high procedural success (> 97 %) and low complication rates (0.5 %).This article represents the third part of a manuscript series designed to improve professional education in the field of cardiac electrophysiology. Mechanistic and clinical characteristics as well as management of isthmus-dependent atrial flutter are described in detail. Electrophysiological findings and catheter ablation of the arrhythmia are highlighted.